60 Takephonership. (12th November 2018) - Deacon, Scott; Wynne-Jones, David
Abstract : Issue: Our inability to answer the phone and resolve patient problems in a timely manner. This manifested as: Poor patient experience Answerphone messages not actioned Incorrect diverting of calls Unnecessary emails between teams Lack of education around the role of admin teams. Bristol Dental Hospital Executive commissioned work to resolve this which had clinical leadership, Consultant Scott Deacon and managerial leadership, Deputy Divisional Director David Wynne-Jones. Strategy for improvement: A task and finish group was setup including clinicians and admin stakeholders.Additional drop in sessions were setup to engage staff and embed a culture of ownership.The initiative was called 'TakePhonership' and the Trust communications team supported creating the brand. The initiative went live with data to highlight problem areas.Drop in sessions were well attended and straightforward actions were implemented.Including: Check telephone number accuracy on website and letters A 'Power Hour' – focussed on the busiest call times Purchasing headsets Educating departments on team roles Embed culture of responsibility Looking at various call routing mechanisms Engaging with centralised call centre Issuing anonymised updates The agreed measurements of improvement were: - Volume of calls -% of overall calls answered -% of overall calls answered when available - Level of telephone related complaints These are reviewed and fed back to teams via email, meetings, and ongoing engagement drop in sessions and leadership walk rounds. Measurement: We now receive under 3000 calls a week; almost halving the call volume.At the height of complaints only 66% of calls were being answered when we were available.This has risen to over 75% and is likely to exceed 80%.Complaints have fallen significantly by 300%. Impact: Bristol Dental Hospital has taken 'phonership' and changed the culture is.This initiative has been adopted across the Trust.